2002
DOI: 10.1063/1.1472470
|View full text |Cite
|
Sign up to set email alerts
|

Josephson effect in Nb/Al2O3/Al/MgB2 large-area thin-film heterostructures

Abstract: We report the demonstration of dc and ac Josephson effects in Nb/Al2O3/Al/MgB2 thin-film heterostructure. The heterostructure exhibits moderately hysteretic current–voltage characteristic with a dc Josephson current branch and regular microwave-induced Shapiro steps. From conductance spectrum, a gap of about 2 meV at 7.7 K is estimated for the proximized surface of MgB2 electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…I C = 290 µA and I C = 110µA were measured in these junctions with R N = 7.4Ω and R N = 18.5Ω, respectively. This implies I C R N = (2.1 ± 0.1) mV at T=4.5K, among the highest values reported in the literature 12,14,27 . Our values are very close to those predicted when the superconducting Nb couples with the MgB 2 π-band 21 and follow the expected Ambegaokar-Baratoff temperature behavior 21,30 .…”
Section: Nb Csupporting
confidence: 62%
See 3 more Smart Citations
“…I C = 290 µA and I C = 110µA were measured in these junctions with R N = 7.4Ω and R N = 18.5Ω, respectively. This implies I C R N = (2.1 ± 0.1) mV at T=4.5K, among the highest values reported in the literature 12,14,27 . Our values are very close to those predicted when the superconducting Nb couples with the MgB 2 π-band 21 and follow the expected Ambegaokar-Baratoff temperature behavior 21,30 .…”
Section: Nb Csupporting
confidence: 62%
“…In comparison with the theoretical predictions 21 , the majority of the reports indicate depressed values of such product and different temperature behaviors irrespectively to the weak link or tunnel nature of the junctions 12,14,26,28,29 . To the best of our knowledge, in the majority of the cases coupling of the conventional superconductor with only the 3D band of the multi-gap material is inferred.…”
Section: Nb Cmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Several groups have already demonstrated tunnel junctions with both lower T c superconductors [4][5][6][7] and with MgB 2 as the top electrode [8][9][10] using different barrier layers such as AlN, MgO, Al 2 O 3 , and the thermal oxide. The results indicate that key issues for fabricating tunnel junctions are the uniform coverage of the base electrode by these barriers, as well as the stability of these barriers when the top MgB 2 electrode is deposited at temperatures ≥300 o C. In junctions with AlN barriers 9 the data suggested that a thermal oxide must be part of the barrier, and that stimulated our work.…”
mentioning
confidence: 99%